Makanan Halal Perspektif Tafsir Ishari Ibnu Ajibah - Hasan, Ziyad; Azis, Fakih Abdul (Mahad Aly Al Fithrah, 2025)
This research examines the formulation of the halālan ṭayyiban food concept through tafsir ishārī (allusive interpretation) as initiated by Ibn `Ajībah. This qualitative study utilizes a library research approach. To achieve the research objectives, the analytical method employed is descriptive-analytical. In terms of theory, this research applies the theory proposed by al-Farmawī. The findings of this study are: firstly, a distinction is found between the apparent meaning of ḥalālan ṭayyiban as physical food and ḥalālan ṭayyiban as ishārī food, which refers to the immaterial nourishment of the human spirit or soul. Secondly, to obtain ḥalālan ṭayyiban spiritual food, one must undergo processes of zuhud (asceticism), wara' (piety/scrupulousness), riyāḍah (spiritual exercise), and mujāhadah (struggle against one's ego). Thirdly, the ḥalālan ṭayyiban nourishment for the human spirit and soul is attained through al-tafakkur (contemplation), al-istibṣār (insight), and al-shuhūd al-‘Iyān (direct witnessing). Fourthly, in order to maintain the spiritual food pattern for the human soul, one must pass through the stages of zuhud, wara', riyāḍah, and mujāhadah. The purpose of maintaining this food pattern is to achieve spiritual health through specific